2020
DOI: 10.1002/adfm.202007921
|View full text |Cite
|
Sign up to set email alerts
|

Metal Halide Scintillators with Fast and Self‐Absorption‐Free Defect‐Bound Excitonic Radioluminescence for Dynamic X‐Ray Imaging

Abstract: Scintillators for radiation detection are of great significance in medical imaging, security, and nondestructive inspection. The current challenge for scintillators is to simultaneously achieve high scintillation light yield, fast radioluminescence, simple film fabrication, large X‐ray attenuation efficiency as well as stable and nontoxic compositions; no previous scintillators fulfill all the above requirements. Here, metal halide Rb2AgBr3, possessing defect‐bound excitonic radioluminescence, is shown as effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 47 publications
3
96
0
Order By: Relevance
“…On the other hand, our calculated band gap (5.10 eV) and STE emission energy (3.692 eV) in Rb 2 AgBr 3 are in excellent agreement with those reported previously (5.1 eV and 3.7 eV). [43] This emission mechanism is also supported by the literature precedent of analogous ternary silver halides. [52] As another supporting evidence for the significant role of defects in determining the photophysical properties of A 2 AgX 3 , previously it was reported that the pulling of vacuum on a Rb 2 AgBr 3 sample significantly increases the intensity of the defect PL peak.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, our calculated band gap (5.10 eV) and STE emission energy (3.692 eV) in Rb 2 AgBr 3 are in excellent agreement with those reported previously (5.1 eV and 3.7 eV). [43] This emission mechanism is also supported by the literature precedent of analogous ternary silver halides. [52] As another supporting evidence for the significant role of defects in determining the photophysical properties of A 2 AgX 3 , previously it was reported that the pulling of vacuum on a Rb 2 AgBr 3 sample significantly increases the intensity of the defect PL peak.…”
Section: Resultssupporting
confidence: 77%
“…[52] As another supporting evidence for the significant role of defects in determining the photophysical properties of A 2 AgX 3 , previously it was reported that the pulling of vacuum on a Rb 2 AgBr 3 sample significantly increases the intensity of the defect PL peak. [43] To test this further, we prepared Rb 2 AgI 3 using two differing techniques: (i) the more reliable method of sample preparation involved annealing of the sample in a vacuum sealed ampoule under 5 mTorr for 80 h, followed by regrinding and reannealing for another 80 h. The second method involved only a short annealing time of 12 h. The PL spectra for resultant samples are starkly different (Figure S11, Supporting Information), suggesting the dominant STE emission for the second sample with short annealing time. The emission energy for this sample matches well with the calculated STE transition energy (Figure S9, Supporting Information and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[ 38,39 ] For computed tomography (CT) imaging, delay‐free imaging aims to reduce the afterglow, [ 40,41 ] as confirmed by Rb 2 AgBr 3 with a lifetime of 5.5 ns as a scintillator for dynamic X‐ray imaging, although a light yield of 21 000 per MeV was observed. [ 25 ] For X‐ray detection, RL should match the response peaks of photodetectors. The emission spectrum of Cu‐doped Cs 2 Agl 3 crystals with blue‐green emission matches with the photodetection efficiency curve of a commercial SiPM, [ 42 ] suggesting an important advantage of Cu‐doped Cs 2 Agl 3 as a scintillator.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] More recently, a lead‐free scintillator with a fast scintillation decay time (5.31 ns) has been utilized for dynamic real‐time X‐ray imaging, suggesting the feasibility of the fast response. [ 25 ] However, the radiation absorption efficiency is lower than those of commercial scintillators despite the relatively high light yield (25 600 photons per MeV). Therefore, metal halide scintillators with high light yield, high absorption coefficient, and fast response time are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] 1D CsCu 2 I 3 and Rb 2 AgBr 3 perovskites were also reported as stable and sensitive X‐ray scintillators with a light yield of 16 000 and 25 600 photons MeV −1 , respectively. [ 11,12 ] Single crystals of Cs 4 EuBr 6 with 0D structure can achieve an ultrahigh light yield of 78 000 photons MeV −1 . [ 13 ]…”
Section: Introductionmentioning
confidence: 99%